2D ANIMATION CREATION WITH BUJANG GANONG ART THEME - Anindhitya, Hanung; Rachman, Anung; Kurniawan, Rendya Adi (Arty: Jurnal Seni Rupa, 2022)
In this day and age, many traditional arts are marginalized. Marginalization according to the Big Indonesian Dictionary can be interpreted as "marginalizing". Many young people are more familiar with foreign cultures than their own culture, one of which is Korean dance. Whereas in East Java itself there are dances that are no less unique, namely the Bujang Ganong Dance contained in the Reog Ponorogo art. In the midst of the rapid advancement of information technology and the creative industry today, animation is one of the most effective informative media in presenting stories and introducing regional arts because it is more attractive to the target market. In the process of making this animation using qualitative methods using primary data in the form of interviews and secondary data using sources from the internet. While in the design of this 2D animation using the design thinking method. Design thinking which has been popularized by David Kelley and Tim Brown has 5 stages in the process, namely empathize, ideate, define, prototype and the last is test. Using design thinking allows writers to collect various information about existing problems so that they are able to develop ideas and create more innovative alternatives.